Captivity-driven microbiota reshaping: A cross-species analysis of divergent patterns in the gut microbiota of giant pandas (Ailuropoda melanoleuca), red pandas (Ailurus fulgens), and Asiatic black bears (Ursus thibetanus) - Lin Xu; Zhengquan Hu; Xin Zhang; Siyuan Zhang; Wenjing Li; Minglei Wang; Ruihong Ning; Wei Guo (PLoS ONE, 2025)
The relative influence of diet, host phylogeny, and environment on animal gut microbiota remains unresolved, particularly for endangered ursids lacking quantitative data. Here, we systematically evaluated the drivers of gut microbial assembly in captive versus wild giant pandas (Ailuropoda melanoleuca), red pandas (Ailurus fulgens), and Asiatic black bears (Ursus thibetanus) using 16S rRNA V4 sequencing. Compared with wild cohorts, captive giant pandas exhibited significantly reduced α-diversity (P < 0.05), whereas captive red pandas and black bears showed significant increases (P < 0.05). Weighted UniFrac-based β-diversity analysis revealed that intra-species distances between captive and wild individuals exceeded those observed between species within either habitat (P < 0.001), indicating profound community restructuring under captivity. At the phylum level, captive animals were dominated by Firmicutes (68.6 ± 23.0%), in contrast to Proteobacteria dominance in wild populations (81.2 ± 17.6%). Genus‐level shifts included an enrichment of Sarcina in captive bears and Streptococcus and Escherichia–Shigella in captive pandas, whereas wild bears and pandas were predominantly enriched in Burkholderia and Pseudomonas, respectively. PERMANOVA attributed 21.6% of community variance to environment (F = 23.62), compared to 12.3% for host phylogeny (F = 6.75) and 3.9% for diet (F = 4.32). These findings demonstrate that captive management is the primary determinant of gut microbiota divergence in giant pandas, red pandas, and Asiatic black bear provide microbiome-based guidance for improving captive husbandry and reintroduction success.